Teacher Competence in Making Learning Media of ICT-Based PowerPoint-iSpring with Emphasis on Three Levels of Representation - Minda Azhar; Minda Azhar (Pelita Eksakta, 2021)
The aim of the Community Partnership Program (PKM) service activity is to increase teacher competency in making learning media of ICT-based PowerPoint-iSpring with emphasis on three levels of representation. The method of PKM was lectures, demonstrations and workshops. The lecture and demonstration methods were used to deliver the topics i.e ICT and internet terminology, three levels representation and 21st century learning, making learning media of PowerPoint-iSpring, using Camtasia software. The practice includes quick tricks of editing images from ebooks, google image, video learning and transferring them to PowerPoint-iSpring learning media.Workshops were to make PowerPoint-iSpring media accompanied by videos of learning, animation of chemical, physical and biological concepts. This activity can improve the knowledge and skills of chemistry teachers using standard chemistry, physics and biology e-books, videos of learning and animation from internet. This community service activities can improve the knowledge and skills of chemistry teachers in integrating a variety of learning resources that can be used to create ICT-based PowerPoint-iSpring with emphasizing on three levels of representation